PERAN GURU DALAM PENDIDIKAN KARAKTER BERBASIS LITERASI KEPADA SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA DAN BUDI PEKERTI KELAS XI DI SMKN 14 BANDUNG - Dede Solehuddin; Latip Aminudin; Nur’ainiyah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
In an effort to foster character in students through the implementation of literacy-based character education. Of course the teacher plays an important role in educating and cultivating good character in his students. This will greatly affect the smooth process of implementing this literacy-based character education. One of them is by continuing to move to find strategies and methods that are considered effective in solving this problem. The application of character education in schools is carried out in different ways based on needs. Because every child has a different character from one another. Therefore this should be a serious concern in realizing this literacy-based character education. The purpose of writing this article is to find out the teacher's role in literacy-based character education for students in the subject of Islamic Religious Education. This approach uses a qualitative descriptive analytical method. The results of the study can be concluded that Islamic religious education teachers can instill literacy-based character education in programmed activities such as the learning process in the classroom, as well as non-programmed activities outside of learning hours such as programs or events held by schools, or organized by various organizations or extracurriculars .